1998
DOI: 10.1002/(sici)1097-4652(199809)176:3<612::aid-jcp18>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Changes in TGF-β receptors of rat hepatocytes during primary culture and liver regeneration: Increased expression of TGF-β receptors associated with increased sensitivity to TGF-β-mediated growth inhibition

Abstract: To clarify the role of transforming growth factor-beta (TGF-beta) and its receptors in hepatocyte growth, we studied the expression of TGF-beta1 and its receptors and the sensitivity to growth inhibition by TGF-beta1 protein in rat hepatocytes derived from resting and regenerating livers. In hepatocytes derived from resting livers, mRNAs for TGF-beta type II receptor (TbetaR-II), insulin-like growth factor-II/mannose 6-phosphate receptor (IGF-II/M-6-PR), and TGF-beta1 increased with time in primary culture. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 63 publications
2
12
0
Order By: Relevance
“…Although many cytokines and growth factors are involved in the onset of liver regeneration, TGF-␤ has been proposed as an important regulatory factor controlling cell proliferation and death through the transcriptional regulation of cell cycle inhibitors and activators (17); however, sometimes cells become refractory to TGF-␤ signaling and can proliferate even in the presence of this cytokine. Several groups and our data show an up-regulation of the T␤Rs during liver regeneration between 24 and 48 h after PH (18). T␤Rs localize to caveolae although the functional consequences of their activation differ depending on the receptor and the cell type considered, even suppressing TGF-␤-mediated signaling in some cases.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Although many cytokines and growth factors are involved in the onset of liver regeneration, TGF-␤ has been proposed as an important regulatory factor controlling cell proliferation and death through the transcriptional regulation of cell cycle inhibitors and activators (17); however, sometimes cells become refractory to TGF-␤ signaling and can proliferate even in the presence of this cytokine. Several groups and our data show an up-regulation of the T␤Rs during liver regeneration between 24 and 48 h after PH (18). T␤Rs localize to caveolae although the functional consequences of their activation differ depending on the receptor and the cell type considered, even suppressing TGF-␤-mediated signaling in some cases.…”
Section: Discussionsupporting
confidence: 52%
“…Interestingly, TGF-␤ is up-regulated during the early regenerative response to PH (18); however, during regeneration, hepatocytes become refractory to TGF-␤ signals, and the liver grows despite its presence (19). TGF-␤ signaling occurs when TGF-␤ binds to and assembles type I and type II serine/threonine kinase receptors (T␤Rs).…”
mentioning
confidence: 99%
“…The return of the receptor expression may be involved in limiting hepatocyte proliferation with insensitivity to TGF-␤ (Chari et al, 1995). The peak of hepatocyte sensitivity to TGF-␤1-mediated growth inhibition was 2 days after PH, and the peak of T␤R-II expression was 4 days after PH (Nishikawa et al, 1998). Our study revealed that T␤R-II expression was decreased 12 hours after PH, with recovery at the 24-hours time point; splenectomy did not affect the expression at the 48-hours time point.…”
Section: Discussionmentioning
confidence: 99%
“…Under normal conditions, hepatocyte proliferation ceases one week after injury and liver mass is restored within two to three weeks. Studies suggest that TGFβ signaling may play an important role in this process [32][33][34] (Figure 2). However, the definitive molecular mechanism(s) that regulate the termination of hepatocyte proliferation during normal liver regeneration is unclear.…”
Section: Liver Regeneration and Progenitor Cell Activationmentioning
confidence: 99%